2016
DOI: 10.1242/jeb.138180
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and energy availability interact to determine flight performance in the Glanville fritillary butterfly

Abstract: Flying insects have the highest known mass-specific demand for oxygen, which makes it likely that reduced availability of oxygen might limit sustained flight, either instead of or in addition to the limitation due to metabolite resources. The Glanville fritillary butterfly (Melitaea cinxia) occurs as a large metapopulation in which adult butterflies frequently disperse between small local populations. Here, we examine how the interaction between oxygen availability and fuel use affects flight performance in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Trehalose can act as an energy reserve for the life activities of insects under stress, such as starvation and dryness (Yasugi et al, 2017). Under various stresses, trehalose accumulation occurs in insects (Fountain et al, 2016;Tamang et al, 2017;Paithankar et al, 2018). This study found that the trehalose content increased extremely significantly 48 h after dsGSK-3 injection (Figure 2C), and the two trehalase activities decreased extremely significantly (Figures 3A,B), showing consistency.…”
Section: Discussionsupporting
confidence: 60%
“…Trehalose can act as an energy reserve for the life activities of insects under stress, such as starvation and dryness (Yasugi et al, 2017). Under various stresses, trehalose accumulation occurs in insects (Fountain et al, 2016;Tamang et al, 2017;Paithankar et al, 2018). This study found that the trehalose content increased extremely significantly 48 h after dsGSK-3 injection (Figure 2C), and the two trehalase activities decreased extremely significantly (Figures 3A,B), showing consistency.…”
Section: Discussionsupporting
confidence: 60%
“…However, flight in the Glanville fritillary is solely fuelled by carbohydrates (rq = 1) (Haag et al 2005), similar to the case of some other insects, such as bees (Suarez et al 2005). Starvation was shown to reduce circulating glucose and trehalose levels in the Glanville fritillary, but no significant change in haemolymph triglyceride levels was found (Fountain et al 2016). These findings suggest that while lipids have an important role in egg production, lipid oxidation may not be used for energy production in this non-migratory species, and the lower CO 2 production would thus indicate a genuinely lower RMR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to temperature, many other factors may constrain butterfly flight at high elevation, including predation pressure, oxygen and energy availability (Fountain et al, 2016), wind, and radiation (Cormont et al, 2011). Wing loading is positively correlated with speed and manoeuvrability (Tennekes, 2009), and we observed that the wing loading increases with elevation, regardless of species (Table 4).…”
Section: Discussionmentioning
confidence: 60%